Target Detection and Identification Performance Using an Automatic Target Detection System. (March 2017) - Reiner, Adam J.; Hollands, Justin G.; Jamieson, Greg A.
Objective: We investigated the effects of automatic target detection (ATD) on the detection and identification performance of soldiers. Background: Prior studies have shown that highlighting targets can aid their detection. We provided soldiers with ATD that was more likely to detect one target identity than another, potentially acting as an implicit identification aid. Method: Twenty-eight soldiers detected and identified simulated human targets in an immersive virtual environment with and without ATD. Task difficulty was manipulated by varying scene illumination (day, night). The ATD identification bias was also manipulated (hostile bias, no bias, and friendly bias). We used signal detection measures to treat the identification results. Results: ATD presence improved detection performance, especially under high task difficulty (night illumination). Identification sensitivity was greater for cued than uncued targets. The identification decision criterion for cued targets varied with the ATD identification bias but showed a "sluggish beta" effect. Conclusion: ATD helps soldiers detect and identify targets. The effects of biased ATD on identification should be considered with respect to the operational context. Application: Less-than-perfectly-reliable ATD is a useful detection aid for dismounted soldiers. Disclosure of known ATD identification bias to the operator may aid the identification process.